Optimal Techno-Economic Design of Standalone Hybrid Renewable Energy System Using Genetic Algorithm - Hlal I.M.; Ramachandaramurthy V.K.; Hafiz Nagi F.; Bin Tuan Abdullah T.A.R. (Institute of Physics Publishing, 2023)
Energy conservation; Environmental technology; Multiobjective optimization; Renewable energy resources; Rural areas; Wind; Wind turbines; Battery energy storages (BES); Cost of energies; Hybrid renewable energy systems; Loss of power supply probability; Remote location; Rural electrification; Sorting genetic algorithm; Techno-economics; Genetic algorithms